Analisis Pengaruh Rasio Jerami Dan Kotoran Sapi Pada Biodigester Terapung Pada Gas Yang Dihasilkan - Attamimy, Haikal; Putra, Guyup Mahardhian Dwi; Sukmawaty, Sukmawaty (Jurnal Agrotek Ummat, 2024)
To address the concerning trend of increasing fossil fuel use due to population growth, it is necessaryto prioritize alternative energy sources like renewable energy.This study aims to analyze the energy parameters produced through biogas formation in a floating drum biodigester, highlighting the potential for sustainable energy solutions.This research method uses experimental research using three treatments of the ratio of straw, water, and cow dung. The parameters observed and analyzed include the amount of biogas produced, biogas pressure, flame length, combustion rate, and calorific value.The experiment results clearly demonstrate that the first treatment was significantly more effective in producing biogas, with a volume of 0.101 m3 or 101 litre, a pressure of 0.0081 atm, a combustion rate of 0.00266 m3/min, a flame length of 38 minutes, and a combustion calorific value of 210,045 joules.In contrast, the second treatment produced a total biogas volume of only 0.0775 m3 or 77.5 litre, at a pressure of 0.0131 atm, a combustion rate of 0.00209 m3/min, a flame duration of 37 minutes, and a combustion calorific value of 184,965 joules. These results provide strong evidence for the superiority of the first treatment in terms of biogas production. The third treatment produced a biogas volume of 0.0771 m3 or 77.1 litre at a pressure of 0.013 atm, with a combustion rate of 0.00214 m3/min, a flame duration of 36 minutes, and a combustion heating value of 164,587.5 joules.